2023
DOI: 10.1186/s12886-022-02744-w
|View full text |Cite
|
Sign up to set email alerts
|

Independent-effect comparison of five crosslinking procedures for Progressive Keratoconus based on Keratometry and the ABCD Grading System using Generalized Estimating Equations (GEE)

Abstract: Purpose Corneal collagen crosslinking (CXL) is an effective treatment for progressive keratoconus. Multiple CXL modalities are clinically available. The present study compared the 1 year outcomes of five types of CXL procedures for progressive keratoconus in a Chinese population using generalized estimating equations (GEE). Methods This retrospective study included 239 eyes in 171 patients with keratoconus who underwent CXL and were followed up for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…In the literature, only a few studies evaluated the applicability of the ABCD staging system in monitoring the efficacy of the standard procedure. In contrast, only one recently published retrospective study investigated its utility in evaluating accelerated protocols and compared the effectiveness of different protocols regarding the ABCD grading system [ 8 , 39 , 40 , 41 , 42 , 43 ]. Danesh and coauthors showed no significant changes in parameters A and D, while parameters B and C significantly increased one year after conventional CXL [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, only a few studies evaluated the applicability of the ABCD staging system in monitoring the efficacy of the standard procedure. In contrast, only one recently published retrospective study investigated its utility in evaluating accelerated protocols and compared the effectiveness of different protocols regarding the ABCD grading system [ 8 , 39 , 40 , 41 , 42 , 43 ]. Danesh and coauthors showed no significant changes in parameters A and D, while parameters B and C significantly increased one year after conventional CXL [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary, there were no significant changes in parameter B. Parameter C significantly progressed while D remained stable one year after the procedure. Recently, in 2023, a retrospective study was published, the first to our knowledge to evaluate the efficacy of five different accelerated protocols regarding the ABCD staging system one-year post-treatment [ 43 ]. The results showed that parameters A and B decreased in the Iontophoresis CXL group.…”
Section: Discussionmentioning
confidence: 99%